Oz - The Fifth Season Episode 1-8 - Kinney, Terry; Morrow, Rob; Bernstein, Adam; Zakrzewski, Alex; Acevedo, Kirk; Hudson, Ernie; Moreno, Rita (Oz - The Emerald City Collection, 2009)
It's a new year ... but just another day in "Oz". The renovations following the fire are complete: the walls are cleaner, the cafeteria is bigger and everything seems fresher ... everything on the outside that is. Inside the hearts and minds of the prisoners, Oz is just as dark and raw as it ever was. Emerald City may look new, but the old, festering feuds are always just around the corner. [www.play.com]